Interaction between alveolar macrophages and epithelial cells during Mycoplasma pneumoniae infection - Xue, Yazhi; Wang, Mengyao; Han, Hongbing (Frontiers in Cellular and Infection Microbiology, 2023)
Mycoplasma pneumoniae, as one of the most common pathogens, usually causes upper respiratory tract infections and pneumonia in humans and animals. It accounts for 10% to 40% of community-acquired pneumonia in children. The alveolar epithelial cells (AECs) are the first barrier against pathogen infections, triggering innate immune responses by recruiting and activating immune cells when pathogens invade into the lung. Alveolar macrophages (AMs) are the most plentiful innate immune cells in the lung, and are the first to initiate immune responses with pathogens invasion. The cross-talk between the alveolar epithelium and macrophages is necessary to maintain physiological homeostasis and to eradicate invaded pathogen by regulating immune responses during Mycoplasma pneumoniae infections. This review summarizes the communications between alveolar macrophages and epithelial cells during mycoplasma pneumoniae infections, including cytokines-medicated communications, signal transduction by extracellular vesicles, surfactant associated proteins-medicated signal transmission and establishment of intercellular gap junction channels.